β-Sitosterol and Gemcitabine Exhibit Synergistic Anti-pancreatic Cancer Activity by Modulating Apoptosis and Inhibiting Epithelial-Mesenchymal Transition by Deactivating Akt/GSK-3β Signaling - Zhang-qi Cao; Xue-xi Wang; Li Lu; Jing-wen Xu; Xiao-bin Li; Guang-ru Zhang; Zhan-jun Ma; An-chen Shi; Yan Wang; Yu-jun Song (Frontiers Media S.A., 2019)
β-sitosterol (BS), a major bioactive constituent present in plants, has shown potent anti-cancer activity against many human cancer cells, but its activity in pancreatic cancer (PC) cells has rarely been reported. Gemcitabine (GEM) is one of the first-line drugs for PC therapy, however, the treatment effect is not sustained due to prolonged drug resistance. In this study, we firstly studied the anti-PC activity and the mechanism of BS alone and in combination with GEM in vitro and in vivo. BS effectively inhibited the growth of PC cell lines by inhibiting proliferation, inducing G0/G1 phase arrest and apoptosis, suppressed the NF- kB activity, and increased expression of the protein Bax but decreased expression of the protein Bcl-2. Moreover, BS inhibited migration and invasion and downregulated epithelial-mesenchymal transition (EMT) markers and AKT/GSK-3β signaling pathways. Furthermore, the combination of BS and GEM exhibited a significant synergistic effect in MIAPaCa-2 and BXPC-3 cells. More importantly, the combined treatment with BS and GEM lead to significant growth inhibition of PC xenografts. Overall, our data revealed a promising treatment option for PC by the combination therapy of BS and GEM.